From Veto Players to Agenda-Setters?: National Parliaments and Their 'Green Card' to the European Commission. Issue 2 (April 2016) - Fasone, Cristina; Fromage, Diane
National parliaments (NPs) had long been excluded from the European integration process and were in many Member States at best kept informed and rarely involved in daily EU affairs. With the Lisbon Treaty and its introduction of the Early Warning System (EWS), as well as the Political Dialogue initiated by former Commission President Barroso, NPs have now become full actors in the EU. Through the Political Dialogue, they can express their opinion on the Commission Annual Work Programme and influence the Commission's agenda. Now, through control of the respect of the principle of subsidiarity, and provided that their reasoned opinions attain the defined thresholds, they can potentially strike down an existing proposal. However the EWS leads to NPs still being constrained to a limited, reactive role: as 'quasi veto-players' and not one of 'agenda-setter'. Recent developments in favour of the introduction of a 'green card' would change this situation profoundly as NPs would eventually be able to prompt the Commission to make legislative proposals on their behalf. This article sheds light on the evolving role of NPs in EU policymaking from the Lisbon Treaty onwards, from veto players to proactive institutions committed to the good functioning of the EU.